Emerging Aedes-borne infections in southern Switzerland: Preparedness planning for surveillance and intervention - Fouque, Florence; Guidi, Valeria; Lazzaro, Mario; Ravasi, Damiana; Martinetti-Lucchini, Gladys; Merlani, Giorgio; Tonolla, Mauro; Flacio, Eleonora (Travel medicine and infectious disease, 2020)
The Preparedness Plan for Surveillance and Interventions on Emerging Vector-Borne Diseases (VBDs) in Southern Switzerland outlines the strategy for preventing and managing potential outbreaks, as well as the surveillance and control activities with a specific focus on Aedes-borne diseases transmitted by Aedes albopictus mosquitoes. The objective of the plan is to provide Public Health Authorities with a framework of preventive and control measures according to the situation and level of epidemic risks. The plan is divided into various phases representing the different steps for all potential situations, ranging from no vectors and no transmission risk to epidemic levels with multiple autochthonous/local cases of hospitalization (and deaths) until the end of the epidemic. An algorithm presents how decisions are taken to move from one phase of the plan to another, with detailed activities for different partners and strategies for each specific phase. The different phases of the plan include activities on disease surveillance and clinical case management, on vector surveillance and control, communication and coordination of activities. The plan is divided into five phases of activities and decision levels. From phase 0 (no cases) to phase 1 (low number of local cases, less than 5), phase 2 (small outbreak with more than 5 local cases), phase 3 (epidemic) and phase 4 (return to no more cases). The plan has been approved by the cantonal authorities and will be submitted to federal authorities. The required implementation tests will begin shortly.